Screening of anticancer activities of crude extracts of unicellular green algae (Chlorella vulgaris) and filamentous blue green algae (Spirulia plantis) on selected cancer cell lines / Mohd Syahril M.Z ... [et al.] - M.Z, Mohd Syahril; O, Roshani; R., Nur hasyimah; M.S, Mohamad Hafiz; M.D, Sharida; H.Y, Ahmed (Universiti Teknologi MARA, Negeri Sembilan, 2012)
Biomass of Chlorella vulgaris and Spirulina platensis were extracted using either ethanol or chloroform and screened for their anticancer activities against selected cancer cell lines.